Accumulation of Persistent Organic Pollutants in Sediment on Tidal Flats in the North of Vietnam - Nhơn, Đặng Hoài; Thạnh, Trần Đức; Nghị, Dương Thanh; Trang, Cao Thị Thu; Kha, Phạm Thị; Anh, Nguyễn Thị Kim; Hải, Phan Sơn (VNU Journal of Science: Earth and Environmental Sciences, 2014)
Abstract: Tidal flats in the North of Vietnam extend from Móng Cái – Quảng Ninh to Kim Sơn - Ninh Bình are studied sedimentation rates by 210 Pb and 226 Ra on CRS model, accumulation of pollutants include organochlorine pesticides, polychlorinated biphenyls, polycyclic aromatic hydrocarbons. On the tidal flats there are two sedimentary processes, which are accretion and erosion. The accretion process is most on the top of tidal flats, sedimentation rates are range from 0.04-15.83 cm/year, highest sedimentation rates are on deltaic tidal flats, the next is on estuary tidal flats, and smallest sedimentation rate is embayment tidal flats. The erosion process are showed on 20-40cm at Ba Lạt tidal flat and some layers from 20 cm until end of cores on Cửa Đáy tidal flats. Accumulation of persistent organic pollutants in sediment on the tidal flats show two trends, the first trend is increasing on the tidal flats in recently years which are PCBs and PAHs, the second trend is decreasing in recently years is organochlorine pesticides. The deltaic tidal flats have not clearly trend of PAHs in sediments. The compounds of organic pollutants over ISQGs level are 4,4’DDT, phenanthrene, flouranthrene, benzo [a] anthracene. Keywords: Tidal flat, 210Pb, sedimentation rate, persistent organic pollutants, North of Vietnam.